Review of Skid Resistance and the Potential Use of Alternative Materials for Pavement Wearing Course - Edwin , Ervin Rangga; Buking, Ron Aldrino Chan @ Ron; Ibrahim , Wan Hashim Wan; Bujang , Zamri; Tirau, Larry Silas (Current Topics and Emerging Issues in Materials Sciences Vol. 1, 2023)
This study aims to address the drawbacks by reviewing prominent alternative materials that have the potential to replace standard aggregate such as granite for pavement wearing course. A well-designed road must be able to deliver strong initial skid resistance and sustain it over the pavement's service life. This is one of the criteria for a well-designed road. Skid resistance is the capacity of the pavement surface to generate sufficient friction when a moving rubber tire of a vehicle passes through it. Locally accessible building materials have a tendency to polish under traffic and provide insufficient friction, therefore they frequently do not meet traditional pavement criteria. The performance of the skid resistance of the road surface changes based on the shape, size, and gradation of the aggregate in the pavement mixture of the surface to be worn, as well as environmental and traffic conditions. According to the results of this study, environmental factors such as seasonal fluctuations, aggregate choice, and pavement textures affect skid resistance. Furthermore, it has been demonstrated that recycled materials, such as steel slag, exhibit excellent strength and endurance, making them higher quality than natural aggregates.